Determinants that drive financial education in Ecuador - Meza, Arelis (2021)
Financial Education enables the strengthening of the administration of people's resources and the finances of their homes (García, Grifoni, López, & Mejía, 2013). In addition, it is an essential instrument of the policy mix for financial stability, timely market regulation, control and protection of the financial consumer (OECD Conference Center, 2018). Likewise, it can favor the economic system by reducing inequality gaps, promoting the creation of more inclusive societies with educated and informed consumers.In this study, a different methodology was applied to those used by some authors in works in the same area, thus, For the Construction of the Financial Knowledge Indicator as a function of Financials, the Structural Equations Model was used by the method of Partial Least Squares (PLS-SEM), which predicts constructs or latent variables and estimates the path relationships from a set of observed data. The PLS-SEM is a second-generation exploratory multivariate technique (Hair et al., 2014).